Comparison between bicarbonate-based and Stewart methods to assess metabolic acid-base disorders in internistic patients. A pilot study - Maria, Valenti; Francesca, Bruno; Shirin, Demma; Marcello, Bruno Cosimo (International Journal of Medicine, 2017)
Aim: To assess the acid-base status in a cohort of internistic patients, using traditional and â€œmodernâ€ methods, to compare their different sensitivity to detect metabolic disorders and to evaluate a possible relationship between classical and alternative parameters.Patients and Methods: 143 assessment of acid-base and electrolytes balance on 121 internistic patients (76 males and 45 females, mean age 73.9 Â± 10,8 years) were examined according to bicarbonate-based and Stewart methods.Results: The traditional method detected 81 cases (56.6 %) of metabolic alkalosis and 15 cases (10.4 %) of metabolic acidosis. The Stewart method detected 92 cases (64.3 %) of metabolic alkalosis and 22 cases (15.3%) of metabolic acidosis.Traditional method failed to detect 11 cases of metabolic alkalosis (chi square = 1.443; p = 0.226), and 7 cases of metabolic acidosis (chi square = 1.118; p = 0.290) when compared to Stewart's method. A significant relationship was observed between Strong Ion Gap (SIG) and Anion Gap corrected for albumin concentration (AGcorr) (r= 0.53; p <0.001).Conclusions: Our result showed that traditional method is useful to assess acid-base status in internistic clinical setting as well as Stewart's method because no significant difference was found between the two approaches. Nevertheless, the light disagreement observed between the two methods suggests that in a small percentage of cases the traditional method can fail to detect metabolic acid-base abnormalities.